2021
DOI: 10.5935/0103-507x.20210056
|View full text |Cite
|
Sign up to set email alerts
|

The 6-Minute Walk Test predicts long-term physical improvement among intensive care unit survivors: a prospective cohort study

Abstract: Objetivo Avaliar a capacidade do Teste de Caminhada de 6 Minutos para predizer a melhora do estado funcional físico em longo prazo de pacientes sobreviventes à unidade de terapia intensiva. Métodos Foram avaliados, de forma prospectiva, entre fevereiro de 2017 e agosto de 2018, em um ambulatório pós-unidade de terapia intensiva, 32 sobreviventes à unidade de terapia intensiva. Foram inscritos consecutivamente os pacientes com permanência na unidade de terapia intensiva … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, we acknowledge that we have not performed a detailed cardiovascular evaluation that might have depicted differences in 6MWD performance, and it is a limitation of our study. Previous studies [17] have shown that 6MWD 4 months after ICU discharge in COVID-19 patients is significantly impaired compared to healthy subjects [36,37]. Other studies have shown that exercise capacity may be impaired 1 year after discharge [28,29,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, we acknowledge that we have not performed a detailed cardiovascular evaluation that might have depicted differences in 6MWD performance, and it is a limitation of our study. Previous studies [17] have shown that 6MWD 4 months after ICU discharge in COVID-19 patients is significantly impaired compared to healthy subjects [36,37]. Other studies have shown that exercise capacity may be impaired 1 year after discharge [28,29,38].…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation, we assessed patients’ physical performances and lung function following the ICU in terms of the 6MWT distance and spirometry. Previous studies have suggested that ICU patients who survived four months after discharge had significantly worse outcomes than the healthy population [ 27 , 28 ]. The 6MWT performance of ICU patients has been studied in severe respiratory disease; ARDS survivors presented significantly reduced 6-min walking distances at six months and one year follow-up [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies reported data for the 6MWT [13,28,30,31,36,38,39,48]. No studies in our review tested the reliability of the 6MWT.…”
Section: -Min Walk Test (6mwt)mentioning
confidence: 96%
“…There was a high certainty of evidence supporting sufficient construct validity. Two studies validated the GLIM against the Subjective Global Assessment (SGA) demonstrating a high level of precision (AUC 0.85-0.93) and agreement (Kappa 0.85) [48,49]. The GLIM at ICU admission was predictive of ICU mortality and hospital length of stay [73].…”
Section: Nutritional Status Global Leadership Initiative On Malnutrit...mentioning
confidence: 97%